An analysis of India's reform dynamics - Kaliappa Kalirajan (Oxford Development Studies, Vol. 32, No. 1, March 2004, 2004)
One important area of development that needs urgent attention in developing countries is poverty alleviation. Urban poverty in India, as in some other countries, is a spillover of rural poverty and about 65 per cent of the labour force is still working in the agricultural sector. To that extent, this paper, though it does not provide a numerical magnitude of poverty per se, advocates policies directly targeting the agricultural sector to reduce poverty. The policy conclusion is that promoting investment and technological progress, along with efficient use of technology in agriculture, are central to reducing poverty.